Association of maternal psychological distress with children with overweight/obesity in Ethiopia. (12th September 2022) - Biadgilign, Sibhatu; Mgutshini, Tennyson; Deribew, Amare; Gelaye, Bizu; Memiah, Peter
Abstract: Background: Poor maternal mental health is a major risk factor for adverse offspring health outcomes, including overweight/obesity status. Maternal mental distress is highly prevalent and associated with parenting practices influencing child weight. To date, there is little information documented in Ethiopia on maternal mental distress and children with overweight/obesity status. This study examined the association between maternal mental distress and children with overweight/obesity among mother–child dyads in Addis Ababa, Ethiopia. Methods: An observational population‐based cross‐sectional study was conducted among mother–child dyads in representative samples in Addis Ababa, Ethiopia. Maternal mental distress was measured using the Self‐Reporting Questionnaire (SRQ)‐20. Child/adolescent overweight/obesity was defined as more than 1 SD above the median World Health Organization (WHO) growth reference. Multivariate logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: The prevalence of maternal mental distress and children with overweight/obesity was estimated to be 10.1% and 28.8%, respectively. After adjusting for confounders, including maternal education, maternal occupation, average monthly household income, maternal body mass index (BMI) and the number of household members/family size, maternal psychological distress was not associated with offspring overweight/obesity status (adjusted OR [aOR] = 0.54; 95% CI: 0.25, 1.14). Conclusions: There is no evidence of an association between maternal psychological distress and children with overweight/obesity. This lack of association might be attributable to our cross‐sectional study design. Future epidemiologic studies, particularly those using prospectively collected data, are warranted to examine better the effects of maternal psychological distress on offspring body weight.